Companions of life : poems from Zimbabwe - Mawere, Munyaradzi (Langaa Research & Pub. CIG, 2012)
This is a dense, erudite collection of finely crafted poems that powerfully reflect on vices such as war, bad governance, deforestation, dissipation, greed, oppression and cruelty. The poems also tackle other important phenomena of life such as love, anxiety, weather, time, politics, morality, economics, justice, culture and the environment. The virtue of these finely tuned poems does not only lie in their philosophical questioning, but their artistic merit and audacious reflection of issues pertinent in human life of all ages. While some of the poems provoke amusement and others tears, the corpus of the collection educates through entertainment. The poetry penetrates into the greater depths of the public's psyche to appraise, query, empty and expose their concerns in such a manner that should hopefully make those who cause or ignite human tribulations to rethink their actions and those haunted by the same to stay vigilant.